Plasmonic devices for on-chip optical interconnects - Ooi, Kelvin Jian Aun (2013)
Continuous scaling of electronic integrated circuits requires the replacement of electrical interconnects with optical interconnects. However, photonic optoelectronic devices are generally large in size, hence hindering smooth electronic–photonic integration. Plasmonics, which allows manipulation of light at the subwavelength scale, would be the key technology to provide the integration platform. Hence, in this research, we have designed plasmonic optoelectronic devices for on-chip optical data transmission on electronic–plasmonic–photonic integration platforms. The first device developed is a monopole antenna-assisted waveguide-coupled cavity detector, which consists of a monopole antenna mounted onto the metal layer of the hybrid plasmonic waveguide end and separated by a feed-gap which forms the detector cavity. The detector has an absorption volume of as small as 220×150×60nm3 and optical power absorption as high as 42%. To our best of knowledge, this is the first waveguide-coupled monopole antenna-assisted cavity detector design. The design offers several practical benefits such as full waveguide-integration and CMOS compatible fabrication process. For the second device, we have continued to enhance the previous detector’s absorption efficiency to 78% by designing plasmonic coupled-cavities, which consists of coupler, detector and reflector cavities arranged in series. The plasmonic coupled-cavities show strong inter-coupling between the three cavities, and hence increase optical power coupling and localization inside the detector unit. The third device we have designed is an ultracompact vanadium dioxide (VO2) dual-mode plasmonic waveguide electroabsorption modulator, which shows low insertion losses of ~1dB, high modulation depths of ~10dB, with ultrashort modulation lengths of ~200nm. The modulator has a potentially ultrafast operating speed and low energy consumption of ~2.6fJ/bit. The high performance is attributed to the use of a mode-switching operation to switch between a low loss hybrid plasmonic mode and high loss MIM mode, enabled by its unique metal–insulator–VO2–insulator–metal (MIVIM) structure. Finally, we have explored doped graphene nanoribbons (GNRs) to build ultracompact active waveguide modulators and optoelectronic devices for mid-infrared operating wavelengths. Graphene surface plasmons are shown to compress mid-infrared wavelengths down by up to two-orders. We have built GNR plasmonic waveguide modulators that show modulation contrasts exceeding 30dB, which are further extended to build GNR active power splitters. The GNR active power splitters are potentially scalable to large and complex active multi-port networks. This opens up a potential possibility of building mid-infrared integrated circuits that operate in deep submicron dimensions. The design of these plasmonic optoelectronic devices may bring forth the realization of practical electronic–plasmonic–photonic integrated circuits, owing to the much reduced device sizes and substantial reduction of energy consumption. In addition, most of the devices can be fabricated by largely CMOS compatible processes, thus making industrial realization possible in the near future.